2016
DOI: 10.1007/s00338-016-1450-z
|View full text |Cite
|
Sign up to set email alerts
|

Large-amplitude internal waves sustain coral health during thermal stress

Abstract: Ocean warming is a major threat for coral reefs causing widespread coral bleaching and mortality. Potential refugia are thus crucial for coral survival. Exposure to large-amplitude internal waves (LAIW) mitigated heat stress and ensured coral survival and recovery during and after an extreme heat anomaly. The physiological status of two common corals, Porites lutea and Pocillopora meandrina, was monitored in host and symbiont traits, in response to LAIW-exposure throughout the unprecedented 2010 heat anomaly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 50 publications
(88 reference statements)
3
29
0
Order By: Relevance
“…The response of the benthic community was unusually rapid. Whereas corals typically bleach – and recover – in response to several months of accumulated heating or cooling2829, corals on the Dongsha reef flat bleached within one week of peak temperatures and 90% of them were either recovered or dead less than six weeks later.…”
Section: Resultsmentioning
confidence: 99%
“…The response of the benthic community was unusually rapid. Whereas corals typically bleach – and recover – in response to several months of accumulated heating or cooling2829, corals on the Dongsha reef flat bleached within one week of peak temperatures and 90% of them were either recovered or dead less than six weeks later.…”
Section: Resultsmentioning
confidence: 99%
“…During warm water events, breaking IGWs can also entrain or mix cooler water into the reef environment. This process reduces heat stress and coral bleaching (Schmidt et al, 2016(Schmidt et al, , 2017Wall et al, 2015), and the associated rapid temperature fluctuations have been shown to condition corals to be more resilient to heat stress (Buerger et al, 2015;Safaie et al, 2018). Areas of intense wave activity thus may be associated with the creation of so-called "thermal refugia" for coral reefs, and because the tides and their attendant IGW generation are not affected by climate change, these refugia may be expected to persist into the future.…”
Section: Introductionmentioning
confidence: 99%
“…The response of the benthic community was exceptionally fast. Whereas corals typically bleach -and recover -in response to several months of accumulated heating or cooling (Liu et al, 2014;Schmidt et al, 2016), corals on the Dongsha reef flat bleached within 1 week of peak temperatures and 90% of them were either recovered or dead less than 6 weeks later.…”
Section: Resultsmentioning
confidence: 99%